Intraoperative portable ultrasonography localization of clinically impalpable soft-tissue tumors - Jagadeesan, Jagajeevan; Davies, Jonathan A.; Raurell, Anna; Ashford, Robert U. (BioMed Central, 2012)
Background: Most soft-tissue tumors are clinically palpable; however, some can be impalpable to clinical examination making it difficult to plan surgical management.